Paranoid metaphors: an examination of the discursive, theoretical and sometimes personal, interaction between the psychoanalyst, Jacques Lacan, the surrealist, Salvador Dali, and the English poet, David Gascoyne - De Klerk, Eugene (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2003)
This thesis examines the historical interaction of the psychoanalyst, Jacques Lacan, the surrealist, Salvador Dali, and the English poet, David Gascoyne. It traces the discursive, and sometimes personal, relationship between these figures which led to a psychoanalytic-based conception of paranoia that impacted on both surrealism and the surrealist-inspired poetry and theory of David Gascoyne. Furthermore it seeks to identify the potential ramifications of this conception of paranoia, and the artistic practice it engendered, for literary, Marxist and psychoanalytic theory.
Keywords: Paranoia; Lacan, Jacques, 1901-1981; Dali, Salvador, 1904-1989; Gascoyne, David, 1916-2001